The Influence of Modernization on the Phenomenon of Sirri Marriage Among Libyan Students from the Perspective of Islamic Family Law - Alfarisi, Salman; Arwani, M. Khairul (Alhurriyah, 2024)
This study explores the impact of modernization on the practice of Sirri marriage among Libyan students, analyzed through the lens of Islamic Family Law. Sirri marriage, an unofficial and unregistered form of marriage, has seen a notable increase among young Libyans, particularly students. The research delves into the underlying reasons for this trend, examining how modernization characterized by rapid social, cultural, and economic changes has influenced students' attitudes and choices regarding marriage. By employing qualitative methods, including interviews and surveys, the study captures personal narratives and broader social patterns. It reveals a complex interplay between traditional values and modern aspirations, highlighting how students navigate their religious obligations and contemporary societal pressures. The findings indicate that modernization has both challenged and reshaped traditional marriage practices, leading to a rise in Sirri marriages as a pragmatic solution to financial constraints and social expectations. Additionally, the study discusses the legal and ethical implications of Sirri marriage within the framework of Islamic Family Law, considering the perspectives of scholars and practitioners. This research contribution offers a valuable insight into the evolving marriage landscape in Libya, providing a nuanced understanding of how modernisation affects young people's decisions and the wider implications for Islamic family law.